Postoperative adhesion formation: the role of peritoneal macrophages and targeting therapy - Liu, Zhong-Yuan; Li, Ren-Feng; Qin, Hong-Yan; Ma, Peng-Fei (Frontiers in Immunology, 2025)
BackgroundPostoperative adhesion (PA) is the most common complication of abdominal or pelvic surgery, resulting in various complications, including small bowel obstruction, secondary female infertility, chronic abdominal pain and even death. Unfortunately, there are few effective methods for the prevention and treatment of it. Previous studies confirmed that coagulation response, inflammation, fibrosis and fibrinolysis played a central role in PA formation and a variety of cells, such as monocytes, macrophages, fibroblasts, neutrophils and mesothelial cells participated in this process. Peritoneal macrophages are prominent immune cells that maintain homeostasis and coordinate cavity wound healing in serosal cavities.Aim of reviewIn this review, we analyze the role of peritoneal macrophages in PA formation. it also presents the latest treatment and prevention strategies targeting peritoneal macrophages. This review focuses to provide an immunological theoretical basis and new target for the prevention and treatment of PA.Key scientific concepts of reviewPeritoneal macrophages recognize sterile or infected injury, initiate repair, form aggregates, and regulate coagulation, inflammation, fibrosis and fibrinolysis in PA formation. Therefore, in the most of existing strategies to prevent PA formation, the biological mechanism is related to the function of peritoneal macrophages. Targeting macrophages to prevent PA formation holds great promise.